2018
DOI: 10.1371/journal.pone.0204364
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy mapped with methylene blue dye alone in patients with breast cancer: A systematic review and meta-analysis

Abstract: BackgroundMethylene blue dye is easy to obtain in developing countries and can be used in sentinel lymph node mapping for breast cancer. However, the accuracy of methylene blue alone for sentinel lymph node mapping in breast cancer has not been well defined. In this study, we collected data to assess the feasibility and accuracy of sentinel lymph node biopsy mapped with methylene blue alone in patients with breast cancer.MethodsWe searched the PubMed, EMBASE, and Cochrane Library databases from January 1, 1993… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 56 publications
2
80
3
3
Order By: Relevance
“…Indeed, one to twelve nodes of the axillary region stained blue (Table 4) in 22 of 26 cases (84.6%). An identification rate that compares favorably with conventional BD guided lymphatic mapping 37 . Although the VX2 study did not investigate the tracer transport to lymphatic drainage, its dispersion along frozen margin and tumor-muscular interface resulted in its interstitial drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one to twelve nodes of the axillary region stained blue (Table 4) in 22 of 26 cases (84.6%). An identification rate that compares favorably with conventional BD guided lymphatic mapping 37 . Although the VX2 study did not investigate the tracer transport to lymphatic drainage, its dispersion along frozen margin and tumor-muscular interface resulted in its interstitial drainage.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis of 18 studies with 1559 patients done by Jiyu Li et al, have reported 91 percent identification rate by methylene blue alone. Hence the authors have concluded by commenting that use of methylene blue alone to localize a sentinel node did not differ substantially when compared with combination method or use of other blue dyes [17]. Unfortunately, the same meta-analysis reported a higher FNR of 13 percent which was far above the accepted false negative rate recommended by the American Society of Clinical Oncologist [15].…”
Section: Slnd In Sri Lankamentioning
confidence: 95%
“…Detecting SLNs is achieved by using lymphatic tracers, most commonly injected peritumorally, that delineate lymphatic tracts to the sentinel nodes 3 . The gold standard in SLN mapping employs dual tracer techniques involving a combination of radioisotopes, blue dyes and/or fluorescence to increase reliability [4][5][6] . However, in specific countries and facilities, methylene blue dye is used alone for SLN mapping in light of its cost effectiveness, accessibility and safe outcomes 4,7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard in SLN mapping employs dual tracer techniques involving a combination of radioisotopes, blue dyes and/or fluorescence to increase reliability [4][5][6] . However, in specific countries and facilities, methylene blue dye is used alone for SLN mapping in light of its cost effectiveness, accessibility and safe outcomes 4,7,8 . Methylene blue is a non-specific blue dye with a good safety profile and has been described for use as an alternative to isosulfan blue and patent blue dye 2,4,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation